The Development of a Multimedia-Based Electronic Booklet for Teaching Reading Skills to Sixth Grade Elementary Students: تطوير الكتيب الإلكتروني القائم على الوسائط المتعددة في تعلم مهارة القراءة لطلاب الصف السادس في المرحلة الابتدائية - Mukhlisah, Mukhlisah; Thaha, Qashdina Alya; Hidayatullah, Wahyu (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2025)
Learning reading skills is one of the most important things to develop students' Arabic language skills. Using appropriate and interesting media can make it easier for them in the process of learning reading skills. One way is by using multimedia-based e-booklets. Therefore, this research aims to develop multimedia-based e-booklets in learning reading skills for class VI SD/MI students to make it easier for them during learning, so that they are more active and creative during the learning process. The method used in this research is R&D (Research and Development) with the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. Based on the results of the development of this media, it received a positive and effective response in helping students understand lessons and practice reading skills.